The Impact of Mind Mapping On Grade Five Students’ Social Science Learning Outcome - Septia, Eko Purwanti, A. Busyairi, Trifosa Veni (Universitas Negeri Semarang, 2018)
The background of this research is the low of Social Science learning result of student because teachers have not applied the learning model in accordance with the regulation. This research aims to know the excellences of Mind Mapping learning model, know the difference learning result of control class and experiment class, test the effect of Mind Mapping learning model on Social Studies learning result. This research type is quasi experiment with Nonequivalent Control Group Design. Population in this research is SD Gugus Mahesa Jenar Ambarawa, Kabupaten Semarang. The sampling technique used is probability sampling with cluster sampling technique, it’s selected SD N Lodoyong 03 as experiment class, and SD N Lodoyong 02 as control class. Mind Mapping learning model as the treatment that given in the experimental class, while the control class used Direct Instruction learning model. Learning result data was analyzed by independent sample t-test. Significance value 0,05 so that H1 is accepted, and ttable is bigger than tcount (14,152 1,672) so there is a average difference learning result between experimental class and control class. In addition, the average pretest of the experimental class is 33, and the control class is 39. While the average posttest of the experimental class is 76, and the control class is 45. Thus, the increased of students' learning result in the experimental class is more than the control class. So, it can be concluded that Mind Mapping learning model is more excellent than Direct Instruction learning model, there are differences in Social Science learning result on experimental class and control class, and mind mapping learning model has an effect on increasing Social Science learning result at 5th grade SD Gugus Mahesa Jenar.